On the benefits of robo-advice in financial markets - Marco Lambrecht; Joerg Oechssler; Simon Weidenholzer (University of Heidelberg, Department of Economics, 2023)
Robo-advisors are novel tools in financial markets that provide investors with low-cost financial advice, usually based on individual characteristics like risk attitudes. In a portfolio choice experiment running over 10 weeks, we study how much investors benefit from robo advice. We also study whether robos increase financial market participation. The treatments are whether investors just receive advice, have a robo making all decisions for them, or have to trade on their own. We find no effect on initial market participation. But robos help investors to avoid mistakes, make rebalancing more frequent, and overall yield portfolios much closer to the utility maximizing ones. Robo-advisors that implement the recommendations by default do significantly better than those that just give advice.
urn:nbn:de:bsz:16-heidok-338303
Keywords: C91; D81; G12; G20; G41; 330; algorithmic trading; experiment; financial markets